Preparation of the bonfire to burn the effigy - Mumbai Archive Project Team (Jio Institute, 2024)
Close to midnight, logs of wood and cow dung cakes are arranged around the base of the effigy in preparation for the bonfire. Camphor is also added to expedite the lighting process.